Analisis Pembuatan Filamen 3D Printing Berbahan Pati Kulit Singkong Dengan Polylactic Acid (PLA) Pada Mesin Ekstruder - Gilbert Doni Ambarita; Andita Nataria Fitir Ganda; Diah Wulandari; Dewi Puspitasari (Madani: Jurnal Ilmiah Multidisiplin, 2026)
PLA is a quite popular type of filament because this material is often used as a raw material for bioplastics which have the ability to decompose naturally. However, the price of PLA filament is also quite high, making it inaccessible to everyone, and there is a weakness in the characteristics of polylactic acid, namely its hydrophobic nature. Cassava peel starch as an alternative additive possesses a hydrophilic nature to cover the weakness of PLA's properties. However, an incorrect combination ratio of the two materials will worsen the structural strength of the PLA and cassava peel starch. The objective of this research is to analyze the tensile strength of polylactic acid material with cassava peel starch at ratios of (PLA) 60:40 (CPS), (PLA) 70:30 (CPS), and (PLA) 80:20 (CPS) on an extruder machine. This research uses a quantitative approach experimental method. The specimen preparation was carried out by first mixing the two materials according to the determined ratio, and then processing them in an extruder machine at a temperature of 160°C. The resulting specimens were tested following the ASTM D2256 standard. The research results show that the (PLA) 80:20 (CPS) ratio has the highest average tensile strength of 44.43 MPa with a tensile strain of 0,0241. Thus, the lower the starch ratio, the better the increase in the obtained tensile strength